2020
DOI: 10.29374/2527-2179.bjvm107220
|View full text |Cite
|
Sign up to set email alerts
|

Chemical immobilization of free-living capybaras (Hydrochoerus hydrochaeris) using ketamine-dexmedetomidine combination and a remote drug delivery system

Abstract: Chemical immobilization of free-living capybaras (Hydrochoerus hydrochaeris) using ketamine-dexmedetomidine combination and a remote drug delivery system Imobilização química de capivaras de vida livre (Hydrochoerus hydrochaeris) usando a combinação cetamina-dexmedetomidina e um sistema de administração remota de medicamentos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…One of the greatest discrepancies found in the literature is reported body weight, which we believe is due to the use of the same information of original reports, as well as the significant differences in weight between capybaras in their natural biomes versus synanthropic animals. An average reported body weight for adult capybara's in the wild is between 40-50 kg (Moreira et al, 2013), whereas some members in agricultural and urban areas were reported with up to 105 kg (Rosenfield et al, 2020), < 100% weight variation. Thus, we suggest considering a differentiation between H. hydrochaeris silvestris to H. hydrochaeris synanthrope, due to the fact of substantial weight variation, in some case > 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the greatest discrepancies found in the literature is reported body weight, which we believe is due to the use of the same information of original reports, as well as the significant differences in weight between capybaras in their natural biomes versus synanthropic animals. An average reported body weight for adult capybara's in the wild is between 40-50 kg (Moreira et al, 2013), whereas some members in agricultural and urban areas were reported with up to 105 kg (Rosenfield et al, 2020), < 100% weight variation. Thus, we suggest considering a differentiation between H. hydrochaeris silvestris to H. hydrochaeris synanthrope, due to the fact of substantial weight variation, in some case > 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting semen through catheterization, as described in detail at the works by Araujo et al (2020) and Rosenfield et al (2020), has become a method of interest, and demanded further training.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the dart bounces off afterwards, it will still deliver the drug successfully [28]. In contrast, a conventional syringe dart requires > 2 cm of penetration for successful delivery [29,30]. As an added practical benefit, microneedle-equipped darts with 3D-printed polymer-encapsulated drugs are smaller and lighter-and can be stored longer-than conventional syringe darts.…”
Section: Microneedle Deliverymentioning
confidence: 99%